Revisión bibliográfica del MTA (Agregado de Trióxido Mineral) vs Biodentine en pulpotomías de dentición temporal - González Ordoñez, Teresa Verónica (2022)
Pulp pulpotomy treatment in primary teeth is a procedure that involves amputation of the coronal portion of the affected or infected dental pulp, and treatment of the root stumps with a medicament. The objective of the present study was to develop a bibliographic review of MTA (mineral trioxide aggregate) versus Biodentine in pulpotomies of primary dentition in which we explained and analyzed the materials by performing a literature search of several scientific articles, bibliographic reviews, case reports, systematic reviews, and randomized clinical trials; Applying the inclusion and exclusion criteria, we selected 52 scientific papers from 2010 to 2021 and we analyzed and organized them into tables designed for this purpose. After the analysis and in response to the proposed objectives, we found the properties of both biomaterials to be highly biocompatible with excellent mechanical and biologicals properties, which characteristics are comparable to those of dental tissue as demonstrated. We demonstrated excellent mechanical and biological properties and biological clinical and radiographic responses in the pulp treatments with MTA and Biodentine, the clinical and radiographic success of vital pulp therapy in clinical cases with follow-ups of 6, 9, 12, 18, and 24 months, with reports of painlessness, acute abscess, fistula, pathological mobility, thermal sensitivity, and the absence of furcal or periapical radiolucency internal or external root resorption, as well as periodontal ligament alteration; however,